Non-linear continuum theories in mechanics and physics and their applications - Rilvil, R.S.; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
P.A. Blythe: non-linear far-field theories in relaxing gas flows.- Meixner: thermodynamics of deformable materials.- A.C. Pipkin: non-linear phenomena in continua.- R.S. Rivlin: an introduction to non-linear continuum mechanics.- G.F. Smith: the generation of integrity bases.
Electronic reproduction.
Keywords: Continuum mechanics; Nonlinear theories; Electronic books